Prevention of endometrial hyperplasia without atypia in women of reproductive age - Mekan R. Orazov (IP Berlin A.V., 2021)
Objective of this review is a systematic analysis of the data available in the current literature on the efficacy and safety of progestogens for the prevention of atypical endometrial hyperplasia (EH) in patients of reproductive age. EH is an excessive proliferation that results in increased volume and changes in endometrial tissue architectonics with an increase in the endometrial glands to stroma ratio of more than 1:1. This review will consider the use of progestogens for the prevention of (EH) based on evidence-based scientific evidence over the past 5 years. The expansion of the range of effective treatment options allows the adaptation of treatment to the needs of patients and offers a personalized approach to their management. Progestogens are an effective and safe method for the prevention of atypical hyperplasia, with a wide range of therapeutic benefits associated with reliable favorable fertility prognosis, especially in young women.